Implementasi Kebijakan Seleksi Terbuka dalam Jabatan Pimpinan Tinggi Pratama di Kota Pekanbaru Provinsi Riau - Achmad Mius (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
Open Selection Policy in First-Top Manager is the implementation of Law Number 5 Year 2014 about State Civil Apparatus (SCA). Open selection purpose to create apparatus who has the professional and based on merit system. Open Selection Policy Implementation in Pekanbaru City is the first policy which implemented in Sumatera Island. This research is using descriptive design with qualitative approach. Research informants is gathering from assessor, local head, head of selection team, SCA whoever joint the selection and SCA who has passed the selection. Data analyzing technique is using descriptive technique with interview, observation and documentation as the data collecting technique. Research result shows that Implementation of Open Selection Policy for First-Top manager in Pekanbaru City is done with the effectivity of communication and clear-share authority for each organ who implementing the policy. Besides that, there are big funds for building assessment center, the suitability of workload and program incentives, and there is indication for time uncertainty in each selection phase. Ideal model for open selection policy in Pekanbaru City is theoretical enrichment from Edwards III’s theory of Policy Implementation with adding environment variable and transparency indicator in communication variable.